A Preliminary Study for Six Sigma Implementation İn Laser in situ Keratomileusis (LASIK) Surgeries - Mehmet Tolga Taner; Gamze Kagan; Ibrahim Sahbaz; Engin Erbas; Sabahat Beyza Kagan (International Review of Management and Marketing, 2014)
The purpose of this study is to show how a private eye care center in Turkey developed a Six Sigma infrastructure to investigate the root causes of complications occuring during LASIK surgeries. To analyze the collected data, main tools of Six Sigma’s Define-Measure-Analyze-Improve-Control(DMAIC) improvement cycle such as SIPOC table, Fishbone Diagram and, Failure, Mode and Effect Analysis were implemented. Experience of the refractive surgeons, type of microkeratome and hygiene of microkeratome were identified to be Critical-to-Quality (CTQ) factors for a successful LASIK surgery. The most frequent complications of LASIK surgeries were found to be dry eye syndrome, subconjunctival haemorrhage and flap edge melt. The process sigma level was found to be 3.7135.